2012
DOI: 10.1007/s10295-012-1104-2
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus casei combats acid stress by maintaining cell membrane functionality

Abstract: Lactobacillus casei strains have traditionally been recognized as probiotics and frequently used as adjunct culture in fermented dairy products where lactic acid stress is a frequently encountered environmental condition. We have investigated the effect of lactic acid stress on the cell membrane of L. casei Zhang [wild type (WT)] and its acid-resistant mutant Lbz-2. Both strains were grown under glucose-limiting conditions in chemostats; following challenge by low pH, the cell membrane stress responses were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
98
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(115 citation statements)
references
References 32 publications
15
98
2
Order By: Relevance
“…Shorter chains have been reported to be unable to span the bilayer or form hydrophobic interactions with other lipids and proteins. As a result, the fluidity of the bilayer was increased due to the motion of the free acyl chain ends (16,41). Therefore, the decreased carbon chain length contributed to the increase in cell membrane fluidity, which was in agreement with our results for fluorescence anisotropy detected by the DPH probe.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Shorter chains have been reported to be unable to span the bilayer or form hydrophobic interactions with other lipids and proteins. As a result, the fluidity of the bilayer was increased due to the motion of the free acyl chain ends (16,41). Therefore, the decreased carbon chain length contributed to the increase in cell membrane fluidity, which was in agreement with our results for fluorescence anisotropy detected by the DPH probe.…”
Section: Discussionsupporting
confidence: 91%
“…Lactic acid bacteria (LAB), a group of bacteria widely employed in the food and pharmaceutical industries, may encounter various stress conditions during industrial processes or survival in the GIT. Several studies have suggested that the regulation of membrane status influences the survival of LAB cells under stress conditions, such as oxidative, heat, cold, acid, and osmotic stresses (10,16,17). However, the responses of the cellular membrane to alterations in the carbon source have not been described for LAB.…”
mentioning
confidence: 99%
“…The increase in intrinsic H 2 O 2 resistance could be associated with the higher percentage of cyclic fatty acids in the membrane (47,48). Previous studies have shown that in response to low pH and osmotic stress, cells modify their membranes through chain length, saturation, and cyclopropanation of fatty acids, which alters the transition temperature of the membrane and makes it less permeable to organic acids and salts (44,45,49). More importantly, cyclopropanation decreases the susceptibility of the cell membrane to lipid peroxidation by stabilizing the unsaturated bond through addition of a methyl group (50).…”
Section: Resultsmentioning
confidence: 99%
“…Fifty milligrams of dried cells was resuspended in an NaOH-methanol-distilled water solution (3:10:10, wt/vol/vol). The sample saponification and methylation and extraction of total fatty acids were carried out as described previously (54). Samples were analyzed by gas chromatography (GC) with a polyethylene glycol capillary column eluted at a flow rate of 29.6 ml/min as described previously (55).…”
Section: Med15b Regulates C Glabrata Acid Tolerance Applied and Envimentioning
confidence: 99%